2017
DOI: 10.1016/j.renene.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Wake characteristics of a TriFrame of axial-flow hydrokinetic turbines

Abstract: An effective way to develop arrays of hydrokinetic turbines in river and tidal channels is to arrange them in TriFrame T M 1 configurations where three turbines are mounted together at the apexes of a triangular frame. This TriFrame can serve as the building block for rapidly deploying multi-turbine arrays. The wake structure of a TriFrame of three model turbines is investigated using both numerical simulations and experiments. In the numerical part, we employ large-eddy simulation (LES) with the curvilinear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…To achieve site-specific optimal wind farm design and operation [86,87], further research from both fundamental and applied points of view needs to be carried out. Such work should focus, among others, on: (1) the role and interaction of the two wake meandering mechanisms for different turbine operational and atmospheric conditions; (2) the physics and models for wake meandering in complex terrain, under offshore conditions with breaking waves [88] and in coastal areas [89]; and (3) extension of the meandering models to the wake of marine and hydrokinetic energy devices (may be of complex configuration [90]) interacting with sediment transport [91,92] and different types of turbulent eddies [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve site-specific optimal wind farm design and operation [86,87], further research from both fundamental and applied points of view needs to be carried out. Such work should focus, among others, on: (1) the role and interaction of the two wake meandering mechanisms for different turbine operational and atmospheric conditions; (2) the physics and models for wake meandering in complex terrain, under offshore conditions with breaking waves [88] and in coastal areas [89]; and (3) extension of the meandering models to the wake of marine and hydrokinetic energy devices (may be of complex configuration [90]) interacting with sediment transport [91,92] and different types of turbulent eddies [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…Vennell et al outlined the following effects, which can be seen because of the deployment of turbines in an array configuration: The performance of the tuned turbine is different than that in an isolated manner. Addition of number of rows to an array may increase or decrease the total output. The power generation can be increased with micro‐designing arrangements. Chawdhary et al carried out a numerical and experimental study to examine the performance of three turbines arranged in the form of triangle in an array to understand the difference in wake formation between an isolated turbine and tri‐frame arrangement and found that the velocity of wake is higher in tri‐frame arrangement than in an isolated turbine but produces less kinetic energy than the isolated turbine whereas the two turbines in the second row produced higher energy. Riglin et al carried out a numerical study on three different array arrangements: two turbines along the flow parallel to each other (ie, side by side), two turbines back to back, and four turbines in nonstaggered manner (ie, two‐by‐two turbines).…”
Section: Review On Hydrokinetic Potential Assessmentmentioning
confidence: 99%
“…Chawdhary et al 78 carried out a numerical and experimental study to examine the performance of three turbines arranged in the form of triangle in an array to understand the difference in wake formation between an isolated turbine and tri-frame arrangement and found that the velocity of wake is higher in tri-frame arrangement than in an isolated turbine but produces less kinetic energy than the isolated turbine whereas the two turbines in the second row produced higher energy. Riglin et al 79 carried out a numerical study on three different array arrangements: two turbines along the flow parallel to each other (ie, side by side), two turbines back to back, and four turbines in nonstaggered manner (ie, two-by-two turbines).…”
Section: Multiple Turbines In Arraymentioning
confidence: 99%
“…Simulations and experimentation of the turbines that have surfaced over the years such as when the axial flow turbines were compared with the cross flow turbines [11][12][13][14][15][16][17]. The axial flow turbine were influenced by a phenomenon which is instable and leads to a significant turbulent flow.…”
Section: Numerical Analysis Of Axial Flow Turbinementioning
confidence: 99%